Regional Vernacular in the Poetry Anthology Jejak Kembara by Roymon Lemosol (Structural Analysis) - Raubun, Angel Welmintje; Lewier, Mariana; Maspaitela, Martha (Universitas Pattimura, 2023)
This type of research is qualitative research, because the data collected is descriptive data. This study aims to describe the local diction contained in the collection of poemsTravel Trails by Roymon Lemosol. The data in this study were obtained through reading and note taking techniques. The analysis techniques in this study are: reading carefully the text of the Batumoli poem, from nunusaku to nusalaut, sapalewa, from Malacca to Maluku, identifying local diction which focuses on three aspects of diction in poetry, namely aspects of vocabulary, aspects of word order, and aspects of the suggestive power of words studies as the building structure of literary works (poetry).